2017
DOI: 10.1525/abt.2017.79.5.344
|View full text |Cite
|
Sign up to set email alerts
|

Biocomplexity: Aligning an “NGSS-Ready” Curriculum with NGSS Performance Expectations

Abstract: Until new materials are available that reflect the conceptual shift in teaching required by the Next Generation Science Standards, teachers will need to evaluate existing materials and consider strategies for adaptation. In this article, we demonstrate one strategy for evaluating pre-NGSS curricula to bring them into alignment with the NGSS Framework. To do this, we retrospectively analyzed materials from a high school capstone course in ecology that were developed prior to the advent of the new standards. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This attention to PEs has been argued to increase instructional coherence (Nordine, Opitz, Fortus, Krajcik, & Neumann, ) and to support integrated implementation of NGSS. It has also been influential in other work including systems for formative assessment (DeBarger, Penuel, Harris, & Kennedy, ; Harris et al, ), elementary curriculum that integrates science and literacy (Wright & Gotwals, ), and specific secondary topics like biocomplexity (Puttick & Drayton, ).…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attention to PEs has been argued to increase instructional coherence (Nordine, Opitz, Fortus, Krajcik, & Neumann, ) and to support integrated implementation of NGSS. It has also been influential in other work including systems for formative assessment (DeBarger, Penuel, Harris, & Kennedy, ; Harris et al, ), elementary curriculum that integrates science and literacy (Wright & Gotwals, ), and specific secondary topics like biocomplexity (Puttick & Drayton, ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Much like many efforts to interpret NGSS using PEs (Krajcik et al, ), many articles report on alignment comparisons using NGSS as its referent and specifically targeting PEs or bundles of PEs. Puttick and Drayton () adapt this approach, again with referent to PEs. Starr and Krajcik () also look at bundles of PEs in their proposed method for comparing modeling activities against NGSS.…”
Section: Review Findingsmentioning
confidence: 99%
“…In their review of studies of NGSS alignment, Fulmer, Tanas, and Weiss pointed out two major questions for any claim of alignment to NGSS: (1) Which component or aspect of NGSS is being referred to in looking for alignment (the referent) and (2) How is the alignment between the referent and curricular material actually being judged? They found that most studies either used the performance expectations as referents (e.g., Krajcik et al, 2014; Puttick & Drayton, 2017) or one or more of the three dimensions (e.g., Capobianco et al, 2018; Kaderavek et al, 2015; J. Smith & Nadelson, 2017).…”
Section: Alignment With the Next Generation Science Standardsmentioning
confidence: 99%
“…In the wake of the appearance of the NGSS, a broad literature has sprung up to help teachers with the challenge. Since teacher professional development seems most effective when it is in the context of curriculum to be taught (Darling‐Hammond, Hyler, & Gardner, 2017), curriculum materials are seen to be crucial mediators for teachers' becoming “standards aligned” (Berk, 2014; Colson & Colson, 2016; Krajcik, 2014; Puttick & Drayton, 2017). This study involves changes in teachers' understanding of their work, and practical experience in trying new materials and new methods, evaluating the results, and refining practice as a result of experience.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Curriculum development has long been an important strategy for innovating in science education (Deboer, 1991), especially in the past half‐century of design and experimentation to transform science education to more authentically reflect science as practiced (Munby, Cunningham, & Lock, 2000; Schwab, 1962). Standards and tests provide only limited guidance to teachers and teacher educators about how to achieve the desired science outcomes; instead a common assumption is that classroom materials, their nature, choice, and implementation are essential mediating tools for the teacher (see, e.g., Berk, 2014; Colson & Colson, 2016; Krajcik, 2014; Puttick & Drayton, 2017). Unfortunately, there is insufficient research on how to design effective curricular materials intended to support the range of teacher use and adaptations likely to be seen during large scale curriculum implementation.…”
Section: Introductionmentioning
confidence: 99%